VI Consensus of the Brazilian Society of Bone Marrow Transplantation (SBTMO) - Consensus on Graft-versus-Host Disease (GVHD) - A. M. Funke, Vaneuza; R. Moreira, Maria Cláudia; Vaz de Macedo, Antonio; Melo, Andresa; Schmidt Filho, Jayr; Fatobene, Giancarlo; B. S. Tavares, Rita de Cássia; M. Silva, Marcia; M. Almeida Macedo, Maria Cristina; Colella, Marcos Paulo; A. R. Colturato, Vergilio; de Souza, Mair Pedro; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
In this 2022 Update of Version 2020 of the VI Consensus of the Brazilian Society of Bone Marrow Transplantation (SBTMO) for Graft-versus-Host-Disease (GVHD), we seek to provide evidence-based guidance on all the novel and clinically relevant advancements in both prophylaxis and therapy of Graft-versus-Host Disease for all of those who delve into the field of Hematopoietic Stem Cell Transplantation.